Pelatihan Manajemen Sumber Daya Manusia Dalam Upaya Meningkatkan Kinerja Organisasi - Nur Aisah, Siti (Jurnal Pengabdian Kepada Masyarakat Al-Amin, 2023)
Training aims to improve employee performance, where employee performance has a major influence on an institution in order to be able to compete. Human Resource Management (MSDM) is the basic capital to achieve goals which can improve employee performance. Training is something that is needed in an effort to improve employee performance, namely MSDM, because quality HR is able to have a positive influence on work productivity, employees and institutions. The problem that exists with employees is that their skills still need to be improved to create awareness about the importance of planning and MSDM, where it is felt that there is still a lack of knowledge and practice regarding HRM in improving the performance carried out. The purpose of this community service is to provide training on MSDM in a simple way which can improve employee performance. The benefit of this activity is to provide knowledge on how to plan control, implementation, MSDM, MSDM functions, and how to exercise control to improve performance. The method used in carrying out this activity is to plan community service activities which include the preparation, planning and evaluation stages. It is hoped that this community service activity can help employees increase understanding and motivation about MSDM to make plans so that performance can be better and optimal.